ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DAERAH - Maudita, Aura Vedareni; Susilo (Journal of Development Economic and Social Studies, 2023)
East Java Province has a fairly high percentage of GRDP rate, in 2022 East Java Province GRDP rate reached 5.34% and made East Java Province became province with the second highest GRDP rate in Java Island. Even though East Java Province has a fairly high level of economic growth, it also has very high economic growth inequality. Besides, the movement of East Java Province's GRDP rate fluctuates with a tendency to decrease from 2011 to 2022. Several components are hypothetically affecting economic growth in a region, such as road infrastructure, labor force, regional own-source revenue, and general allocation funds. This study aims to find out correlation between the four aspects to economic growth in East Java Province. The research was conducted using the panel data regression estimation technique and using 38 districts/cities in East Java Province from 2017 to 2021 as a sample. The total sample used was 190 observations. The results of the study show that road infrastructure, labor, regional own-source revenue, and general allocation funds have a positive and significant impact on economic growth in East Java Province.